(3HgLI GdSGdc hGdeSdhc aj JGQjN GdNdaGA hGdSdGWjf hGdedhcs - (3fGUQ GdOjf CHi YHO Gddg eMeO Hf eMeO GdMSf GdLYaQis; (3CHh YHO Gddg eMeO Hf eMeO Hf eMeO GdMSf GdLYaQj GdTGaYj, fGUQ GdOjf,J (B788 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdCeGe GdLhRi GdTGaYi CeG HYO MeO Gddg GjGe ehdGfG GdSdWGf GdGYXe s
(3BNQgG (B:s
(3hbGd gPG YHO QH eMeO GdLYaQi GdTGaYi eMeO ef HYO MeO Gddg hGdUdGI Ydi GdfHi GdcGed GdUaGJ s
(3fSNI NRGFfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B53 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B52 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjg HGQjS (B(1607) s
Keywords: (3GdJGQjNs